Comparative analysis of neuroretinal alterations between patients with type 2 diabetes mellitus without evidence of diabetic retinopathy and a healthy control group - Picco Pérez , Rubén Darío; Vera Duarte, Guillermo Raúl; Fernández , Sara; Castillo Benitez, Verónica Elisa; Arrúa Caballero, Martín Fernando; González-Sanabria, Luis (Medicina Clínica y Social, 2025)
Introduction: Type 2 Diabetes Mellitus (T2DM) causes insulin resistance and can lead to complications like Diabetic Retinopathy (DR), affecting vision. Optical Coherence Tomography (OCT) enables early detection. Objective: The study aimed to compare neuroretinal alterations between patients with Type 2 Diabetes Mellitus (T2DM) without evidence of Diabetic Retinopathy (DR) and a healthy control group. Methodology:  The study included 220 eyes from 110 patients with T2DM without DR and 220 eyes from 110 healthy controls. Detailed interviews, comprehensive ophthalmologic evaluations, and Optical Coherence Tomography (OCT) were used to measure the thickness of the retinal nerve fiber layer (RNFL) and the ganglion cell-inner plexiform layer (GC-IPL). Results: Patients with T2DM showed significant thinning of the RNFL and GC-IPL compared to healthy controls. The average RNFL thickness in T2DM patients was 92.89 ± 7.87 µm, while in controls it was 97.28 ± 11.1 µm (p < 0.001). The GC-IPL thickness in T2DM patients was 80.03 ± 3.58 µm, compared to 81.09 ± 4.09 µm in controls (p < 0.001). Conclusion: There are significant differences in retinal layers between patients with T2DM without evidence of DR and healthy controls. These findings highlight the importance of early and continuous retinal monitoring in T2DM patients to prevent the progression of DR.